Determination of Chemical Composition and Ant-nutritive Components for Tanzanian Locally Available Poultry Feed Ingredients - Mutayoba , S.K.; Dierenfeld, E.; Mercedes, V.A.; Frances, Y.; Knight, C.D. (International Journal of Poultry Science, 2011)
Information on nutritive value of locally available feed ingredients is scarce, therefore chemical composition, TAA, ANF and OSI for eleven feed ingredients commonly used in Tanzania were determined. Standard AOAC Official Methods were performed at the US headquarters of Novus International, Inc. The ingredients were cereals/byproducts (BR, RS, WS1, WS2 and MB), leaf meals (MOLM, GLM and LLM) and oil seed meals/by products (SBM, SCM and CSM). Significant differences for CP, NDF, ADF, minerals, TAA and ANF were observed between nutrient groups. Apart from energy most of the chemical components were lower in cereals; CP and TAA were highest in SBM. CSM contained the highest fat content (35.82%) with high oleic (22.63%) and linoleic (50.59%). The observed chemical differences between (BR and MB) were probably due to their differences in physical composition. Low levels (Ca, Na and P) and EAA were noted in all groups emphasizing the need of using synthetic sources during feed formulation. Total phenols and tannins were (7.71-7.26%) and (2.55-1.02%) for GLM and RS, respectively, but negligible in other feed ingredients. Both HCN and OSI were highest in leaf meals but negligible in other feed ingredients. The chemical composition of ingredients obtained in this study was comparable to values reported elsewhere. This means that optimum diets for livestock can be formulated using ingredient values from established tables and other sources. The present results show that feed ingredients of plant origin vary in their chemical composition therefore they complement each other when used in mixtures of animal diets.